A Validation Study for POSSUM and EuroSCORE as a Predictor of Mortality After Selective Cardiac Surgery - Saeid Saeidimehr1 Saeid Saeidimehr1; Ahmad Ebadi; Farhad Kalantari; Mehdi D Firoozabadi; Fakher Rahim (Acta Medica Indonesiana)
Aim: to assess physiological and operative severity score for the enumeration of mortality (POSSUM) scoring system and compare it with European system for cardiac operative risk evaluation (EuroSCORE) scores in patients who underwent cardiac surgery from two hospitals in the southwestern region of Iran. Methods: in this retrospective study, total of all 1420 patients who were admitted for elective cardiac surgery at our centers, from 2007 to 2012, were scored using the POSSUM and EuroSCORE systems. Results: the overall mortality rate was 0.87%. Among the risk factors, history of diabetes, smoking, respiratory disease, and myocardial infarction, were significantly affect the mortality rate. Therefore, of these risk factors, only the hemoglobin was significantly correlated with the morbidity rate. The predictive accuracy of mortality equations was 74.5%. The lower predictive accuracy of mortality equations was 67.8% was observed using EuroSCORE. Conclusion: although results are statistically significant, but the analysis have never intended to affect the decision to operate, and this decision must be based on clinical expertise, because of the need to standardize data collection and stratify the risks involved in operations, scoring systems such as POSSUM should be used prospectively. However, if analyzed correctly, POSSUM is a good predictor of mortality in patients undergoing cardiac surgery. Key words: cardiac surgery, physiological and operative severity score for the enumeration of mortality (POSSUM), European system for cardiac operative risk evaluation (EuroSCORE).